2020
DOI: 10.1210/clinem/dgaa955
|View full text |Cite|
|
Sign up to set email alerts
|

Genotype–Phenotype Correlations in Central Precocious Puberty Caused by MKRN3 Mutations

Abstract: Context Loss-of-function mutations of makorin RING finger protein 3 (MKRN3) are the most common monogenic cause of familial central precocious puberty (CPP). Objective To describe the clinical and hormonal features of a large cohort of patients with CPP due to MKRN3 mutations and compare the characteristics of different types of genetic defects. Methods Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 21 publications
2
16
0
4
Order By: Relevance
“…The two boys presented with testicular enlargement (testicular size of more than 5 ml) and Tanner stage 2 of puberty before the age of 9 years. Results from the present, in conjunction with previous studies from our group (14,34), indicated that pathogenic (Table 2) or variants of uncertain significance (VUS) (Table 3) in the MKRN3 gene are the most prevalent cause of CPP in our cohort of Cypriot patients, in line with the current published literature (12). The MKRN3 p.Gly312Asp pathogenic variant, first reported in 2016 by Neocleous et al (14), was the most predominant genetic defect (seven cases) of the present study, followed by the previously reported p.Met268ValfsTer23 pathogenic variant identified in four cases (25) (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The two boys presented with testicular enlargement (testicular size of more than 5 ml) and Tanner stage 2 of puberty before the age of 9 years. Results from the present, in conjunction with previous studies from our group (14,34), indicated that pathogenic (Table 2) or variants of uncertain significance (VUS) (Table 3) in the MKRN3 gene are the most prevalent cause of CPP in our cohort of Cypriot patients, in line with the current published literature (12). The MKRN3 p.Gly312Asp pathogenic variant, first reported in 2016 by Neocleous et al (14), was the most predominant genetic defect (seven cases) of the present study, followed by the previously reported p.Met268ValfsTer23 pathogenic variant identified in four cases (25) (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…At this time, genetic aberrations associated with the Makorin Ring Finger Protein 3 (MKRN3) gene are the leading genetic etiology of CPP (9). Since the groundbreaking discovery of loss-of-function mutations in the MKRN3 gene (11), numerous other studies followed and reported more than 40 novel variants, including missense, nonsense, and frameshift mutations in MKRN3 across families with CPP in a broad spectrum of geographical regions (9,12). MKRN3 gene is located in the Prader-Willi syndrome (PWS)-related region (15q11-q13) on chromosome 15.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the inter-relationship among obesity, CPP, and some of these genetic causes. Obesity has not been shown to be associated (positively or negatively) with MKRN3 mutations, the most common monogenic cause of CPP [ 113 , 114 ]. However, obesity is a common finding among children with DLK1 mutations [ 115-118 ].…”
Section: Areas Of Uncertainty and Future Directionsmentioning
confidence: 99%
“…Patients with such 'organic' forms of CPP have a moderately high BMI SDS at CPP diagnosis, similar to that of patients with isolated forms of CPP (6,7,8). In addition, studies of patients with monogenic CPP due to makorin RING finger protein 3 (MKRN3) loss of function, affecting the regulation of the hypothalamopituitary-gonadal axis, have also been reported to have a BMI SDS at the presentation that is moderately high and similar to that of patients with isolated and idiopathic CPP (9,10).…”
mentioning
confidence: 82%